Dual-edged mechanisms of α-tomatine in hepatocellular carcinoma by suppression of Wnt/β-catenin signaling versus RelB-Driven resistance in tumor therapy - Wang, Tianzhen; Xu, Chenyue; Yuan, Yanling; Zhang, Bianhong (Frontiers in Pharmacology, 2025)
BackgroundThe plant-derived steroidal alkaloid α-tomatine has emerged as a promising pan-cancer therapeutic agent, its multifaceted biological effects in HCC remain unexplored. This study aims to decipher α-tomatine’s molecular duality in HCC, resolving its paradoxical capacity to simultaneously activate tumor-suppressive signaling and provoke chemoresistance networks, ultimately establishing synergistic phytotherapy strategies.MethodsHepG2 and SMMC-7721 hepatocellular carcinoma cells were exposed to α-tomatine to evaluate dose-dependent effects on proliferation, migration/invasion, and cell cycle distribution. Transcriptomic profiling via RNA sequencing identified dysregulated pathways. Pharmacological interventions using Wnt3a (activation) and XAV939 (inhibition) modulated Wnt/β-catenin signaling, while CRISPR/Cas9-mediated RelB knockout and plasmid-based overexpression established isogenic cell models. These interventions were subsequently applied in BALB/c nude mouse xenografts, where tumor volume was longitudinally monitored during α-tomatine treatment.Resultsα-Tomatine demonstrated dose-dependent suppression of hepatocellular carcinoma cell proliferation, migration, and invasion, concomitant with G2/M phase arrest. Mechanistically, it exerted Wnt/β-catenin inhibition via β-catenin phosphorylation/degradation while paradoxically inducing RelB-mediated reduction of anti-tumor activity. Wnt activation attenuated therapeutic effects, whereas Wnt inhibitors enhanced efficacy. Genetic RelB ablation potentiated α-tomatine’s anti-tumor activity, contrasting with resistance in RelB-overexpressing models. Xenografts confirmed enhanced suppression in RelB-deficient tumors.ConclusionThis plant-derived alkaloid exerts anti-HCC effects through Wnt pathway modulation, while compensatory RelB activation constrains therapeutic outcomes. Strategic RelB co-targeting establishes a dual pathway phytotherapy paradigm, synergistically merging botanical pharmacodynamics with precision oncology.